Development of a real‐time in vivo dosimetry tool for electron beam therapy using a flexible thin film solar cell coated with scintillator powder. Issue 1 (4th September 2022) - Jeong, Seonghoon; An, Seohyeon; Kwon, Yong‐Cheol; Pak, Sang‐il; Cheon, Wonjoong; Shin, Dongho; Lim, Young Kyung; Jeong, Jong Hwi; Kim, Haksoo; Lee, Se Byeong
Abstract: Purpose: A real‐time solar cell based in vivo dosimetry system (SC‐IVD) was developed using a flexible thin film solar cell and scintillating powder. The present study evaluated the clinical feasibility of the SC‐IVD in electron beam therapy. Methods: A thin film solar cell was coated with 100 mg of scintillating powder using an optical adhesive to enhance the sensitivity of the SC‐IVD. Calibration factors were obtained by dividing the dose, measured at a reference depth for 6–20 MeV electron beam energy, by the signal obtained using the SC‐IVD. Dosimetric characteristics of SC‐IVDs containing variable quantities of scintillating powder (0–500 mg) were evaluated, including energy, dose rate, and beam angle dependencies, as well as dose linearity. To determine the extent to which the SC‐IVD affected the dose to the medium, doses at R90 were compared depending on whether the SC‐IVD was on the surface. Finally, the accuracy of surface doses measured using the SC‐IVD was evaluated by comparison with surface doses measured using a Markus chamber. Results: Charge measured using the SC‐IVD increased linearly with dose and was within 1% of the average signal according to the dose rate. The signal generated by the SC‐IVD increased as the beam angle increased. The presence of the SC‐IVD on the surface of a phantom resulted in a 0.5%–2.2% reduction in dose at R90 for 6–20 MeV electron beams compared with the bare phantom. Surface doses measured using the SC‐IVD system and Markus chamber differed by less than 5%. Conclusions: The dosimetric characteristics of the SC‐IVD were evaluated in this study. The results showed that it accurately measured the surface dose without a significant difference of dose in the medium when compared with the Markus chamber. The flexibility of the SC‐IVD allows it to be attached to a patient's skin, enabling real‐time and cost‐effective measurement.